Ohmic heating in food processing (CRC Press, 2014)
Ohmic heating provides rapid and uniform heating, resulting in less thermal damage than conventional heating and allowing manufacturers to obtain high-quality products with minimum sensorial, nutritional, and structural changes. Ohmic Heating in Food Processing covers several aspects of Ohmic heating: science and engineering, chemistry and physics, biochemistry and nutrition, quality and safety, and development and technology, both basic and applied. It describes the importance of Ohmic technology and how to implement it in practice, addressing basic theory, principles, and applicati.